(untitled) (International Journal of Engineering and Computer Science, 2017)
: This paper presents an interactive model based system for the management of production and controlling process in spinning mill using embedded system and Internet of Things. This system consists of various sensors to measure and store different parameters that are calculated to find the production rate. Apart from a comprehensive presentation of the set of the modules the system is composed of, together with their interrelationships, the above characteristics are analyzed, and their impact on the production control system is explained.. The system is also related to two control process namely air cooler controller and moisture mixer sprayer controller. This process is currently done manually which is being automated.Making Automated in this system we can effectively control the quality of the yarn that is produced in those alike industries. The system’s attributes are presented with the aid of data structure diagrams, while the complete algorithm concerning the arduino module, in a algorithm form is provided and it presents a survey of all such systems.